Optimal production planning and scheduling, case study: Guinness Ghana Brewery Limited, Kumasi - Derkye, Adom (2014)
A thesis submitted to the Institute of Distance Learning, Department of Mathematics in partial fulfilment of the requirement for the award of the Master of Science degree in Industrial Mathematics.